Intensional Kleene and Rice theorems for abstract program semantics - Baldan, Paolo; Ranzato, Francesco; Zhang, Linpeng (Information and computation, 2022)
Classical results in computability theory, notably Rice's theorem, focus on the extensional content of programs, namely, on the partial recursive functions that programs compute. Later work investigated intensional generalisations of such results that take into account the way in which functions are computed, thus affected by the specific programs computing them. In this paper, we single out a novel class of program semantics based on abstract domains of program properties that are able to capture nonextensional aspects of program computations, such as their asymptotic complexity or logical invariants, and allow us to generalise some foundational computability results such as Rice's Theorem and Kleene's Second Recursion Theorem to these semantics. In particular, it turns out that for this class of abstract program semantics, any nontrivial abstract property is undecidable and every decidable over-approximation necessarily includes an infinite set of false positives which covers all the values of the semantic abstract domain.